Theory of periodic conjugate heat transfer - Zudin, Yuri. B. (Springer, 2016)
This book presents the theory of periodic conjugate heat transfer in detail. It offers a simplified description of the interaction between a solid body and a fluid as a boundary value problem of the heat conduction equation for the solid body.
Keywords: Heat -- Transmission.; Heat -- Conduction.; Heat -- Convection.; elektronické knihy; electronic books